2022
DOI: 10.2147/jbm.s367660
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Distribution Width as Novel Biomarker in Cardiovascular Diseases: A Literature Review

Abstract: Red blood cell distribution width (RDW) is a measure of the change in size of red blood cells and it is used in combination with other hematological parameters for the differential diagnosis of anemias. Recent evidence suggested that the change in RDW level may be a predictive biomarker of morbidity and mortality in cardiovascular diseases (CVDs). Cardiovascular diseases are the most common cause of death globally as compared to cancer and communicable diseases. Early diagnosis and prompt intervention of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…Despite the differences in group means being statistically significant, there may be considerable overlap between individual results in the disease and control groups, impacting the meaningfulness of test results. This is particularly noteworthy for the studies of Arkew et al and Jabeen et al, 1 , 5 , 7 where the differences in group means are ~1 fL, despite the statistically significant difference between the two cohorts. Without a rigorous control of the preanalytical and analytical phase variables, individual patient results may be difficult or impossible to interpret.…”
Section: Dear Editormentioning
confidence: 87%
See 1 more Smart Citation
“…Despite the differences in group means being statistically significant, there may be considerable overlap between individual results in the disease and control groups, impacting the meaningfulness of test results. This is particularly noteworthy for the studies of Arkew et al and Jabeen et al, 1 , 5 , 7 where the differences in group means are ~1 fL, despite the statistically significant difference between the two cohorts. Without a rigorous control of the preanalytical and analytical phase variables, individual patient results may be difficult or impossible to interpret.…”
Section: Dear Editormentioning
confidence: 87%
“…Daves et al have reported that time delays as short as 3 hours have resulted in an erroneous RDW result. 10 A lack of control for these preanalytical phase variables may account in part for the different cutoffs for the RDW and the lack of statistical significance in the study of Adane et al 3 Due to the lack of standardization of the RDW across different instrumentation platforms, the wide variety of instruments used in these studies, including devices manufactured by Sysmex (Kobe, Japan), 3 , 6 Abbott (Chicago, IL, USA), 4 Beckman Coulter (Brea, CA, USA), 1 , 5 and Horiba (Kyoto, Japan), 7 may add additional biases.…”
Section: Dear Editormentioning
confidence: 99%
“…Since it has been demonstrated that a strong, positive, and independent association exists between RDW and conventional inflammatory biomarkers (73) several studies have been developed and have confirmed RDW as an interesting variable for inflammatory predictor in various disorders including functional bowel conditions, autoimmune diseases, malignancy, COVID-19 and multiple hospital admissions in subjects with chronic conditions (69). In agreement with the present study, Karakilcik et al, (2014) and Semba et al, (2010) demonstrated a close association between RDW and biomarkers of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this relationship is the fact that oxidative stress exerts a profound effect on red blood cell homeostasis, such as a change in size, increasing its heterogeneity and therefore RDW (74,75). Therefore, oxidative stress increased red cell turnover, thus contributing to the association between anisocytosis and human pathology (69).…”
Section: Discussionmentioning
confidence: 99%
“…Characterizing cell populations or immunophenotyping is a prevalent method for disease diagnosis from surface biomarkers using microfluidic arrays for label-free phenotyping [416] and interaction between RBC Glycophorin and leukocyte surface lectins activation [417].Other studies related to drug delivery assess the interaction mapping between RBCs and drug carriers via image analysis [418], capture and release of circulating tumor cells [419], drug-induced erythrocyte deformation [420], antibodies and biotinlabeled RBC effect on posttransfusion survival [421], shear-induced encapsulation in drug delivery [422], and anti-tumor applications incorporating RBCs and nanoparticles [423]. For COVID-19 related research, RBCs, as oxygen carriers, were analyzed for respiratory issues in COVID-19 patients for RBC deformability/morphology effect on tissues oxygen supply [424][425][426][427][428].…”
Section: Antibody Binding and Drug Discovery Applicationsmentioning
confidence: 99%